Assessment of knowledge of acute kidney injury among non-nephrology healthcare workers in North-Kivu Province, Democratic Republic of the Congo - Kahindo, Charles Kangitsi; Mukuku, Olivier; Wembonyama, Stanis Okitotsho; Tsongo, Zacharie Kibendelwa (Journal of Clinical Nephrology, 2022)
Background: Assessment of knowledge of acute kidney injury (AKI) among healthcare workers (HCWs) is necessary to identify areas of deficiency and key topics to focus on while organizing educational programs to improve AKI care. The objective of this study was to assess AKI knowledge and practice among health care providers in North Kivu province, the eastern Democratic Republic of the Congo. Material and methods: This was a cross-sectional study conducted in six public hospitals in North Kivu province using a self-administered questionnaire. Results: A total of 158 HCWs completed the survey, among them 66 (41.78%) were physicians. The mean age of respondents was 36.07 ± 10.16 years and the male gender was 56.33%. Only 12 (7.59%) of the respondents had a good knowledge of the definition and classification of AKI. The respondents’ mean scores were 6.76 out of a total of 18 about risk factors for AKI and 6.29 out of a total of 11 with regard to nephrotoxic drugs. Regarding practices, 28.48% of the respondents assess the risk of AKI in their patients in their daily practices; 31.65% report AKI in the patients’ medical history, and 33.54% call on a nephrologist specialist to get specialized advice. Conclusion: This study found considerable gaps in knowledge and practice regarding AKI among most of HCWs in North Kivu province.